2018
DOI: 10.2174/1874210601812010094
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cone Beam Computed Tomography Dose in Pre-Surgical Implant Analysis

Abstract: Objectives:Cone-Beam Computed Tomography (CBCT) produces vital information required for the accurate and prudent placement of dental implants. Lack of standardization between CBCT machines may result in unsafe patient exposure to harmful radiation; higher doses are not necessarily associated with improved image quality.Aim:The study aimed to assess the influence of low- and high-dose milliamperage settings on CBCT images for objective and subjective implant planning.Methods:Two dry skulls (4 hemi-maxillary seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In the current study; using ultra-low-dose CBCT (by reducing the milliamperage setting 3.2 mA) did not lower the image quality nor the accuracy of linear measurements. El Sahili et al, 2018, 20 found high degrees of concordance between low and high dose images, and images taken at lower milliamperage settings showed good diagnostic quality.…”
Section: Resultsmentioning
confidence: 99%
“…In the current study; using ultra-low-dose CBCT (by reducing the milliamperage setting 3.2 mA) did not lower the image quality nor the accuracy of linear measurements. El Sahili et al, 2018, 20 found high degrees of concordance between low and high dose images, and images taken at lower milliamperage settings showed good diagnostic quality.…”
Section: Resultsmentioning
confidence: 99%
“…It offers beneficial information for selection of the final implant size and location, and allows the clinicians to assess the amount, density and quality of bone, ultimately enabling optimal implant placement without traumatizing the vital structures such as the mandibular canal, the inferior alveolar nerve, the mandibular posterior lingual undercut, and the maxillary sinuses. 8 Accurate assessment of bone volume and shape, along with clinical evaluations and palpation of the bone ridge at the implant placement site, are essential prior to implant insertion. 9,10 In oral implantology, the most serious and frequent complications described in the literature occur during surgery, and may result from inadequate preoperative assessment, poor implant orientation, or the surgical procedure itself.…”
Section: Introductionmentioning
confidence: 99%